A 3D printing material, preparation method and application thereof in shoe materials
By using a formula combining TPU with polycaprolactone in 3D printing materials, adding nanosilver powder and functional additives, combining carbon nanotubes and nanoconvex rod agents and modified filler supplements, the difficulty of balancing and coordination improvement of 3D printing material shoes in the prior art in terms of antibacterial, wear resistance and mechanical tensile properties is solved, and the product's weather resistance and washing resistance are significantly improved.
Patent Information
- Application Number
- CN202411721589.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Shoe materials prepared from existing 3D printing materials have difficulty in balancing and coordinating improvement in terms of antibacterial properties, wear resistance and mechanical tensile properties. At the same time, poor weather resistance and water washing resistance are poor, which limits the efficiency of the product.
TPU and polycaprolactone are used as the main raw materials, and functional additives such as nanosilver powder, compatibility agents, lubricants, antioxidants are added, combined with carbon nanotubes and nanoconvex rod agents and modified fillers to re-adjust the re-adjustment of modified fillers. Through the modification liquid and ultrasonic modification treatment, the dispersion and activity performance of the raw materials are optimized, and the performance coordination and stability of the product are improved.
The antibacterial, wear resistance and mechanical tensile properties of 3D printing materials have been significantly improved, making them excellent in weather resistance and water washing stability, and improving the efficiency of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of printing materials, and in particular to a 3D printing material, a preparation method and application thereof in shoe materials. Background Art
[0002] 3D printing, also known as rapid prototyping technology or additive manufacturing technology, is a technology that does not require traditional tools, fixtures, and machine tools. Instead, it uses digital model files as the basis and uses adhesive materials such as metal powder or plastic to print layer by layer to manufacture objects of any shape.
[0003] In order to improve the antibacterial property of the existing shoe materials made of 3D printing materials, nano inorganic silver antibacterial raw materials are added to them. However, the raw materials are easy to agglomerate, which can easily lead to poor wear resistance and mechanical tensile properties of the products. At the same time, the antibacterial, wear resistance and mechanical tensile properties are poorly balanced and improved, and the weather resistance and water washing stability of the products are poor, which limits the efficiency of product use. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a 3D printing material, a preparation method and application thereof in shoe materials, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a 3D printing material, comprising the following raw materials in parts by weight:
[0007] TPU 35-40 parts, polycaprolactone 10-15 parts, nano silver powder 6-9 parts, compatibilizer 3-5 parts, foaming agent 3-4 parts, cell stabilizer 2-3 parts, lubricant 1-3 parts, antioxidant 1-3 parts.
[0008] Preferably, the 3D printing material comprises the following raw materials in parts by weight:
[0009] 37.5 parts of TPU, 12.5 parts of polycaprolactone, 7.5 parts of nano silver powder, 4 parts of compatibilizer, 3.5 parts of foaming agent, 2.5 parts of cell stabilizer, 2 parts of lubricant, and 2 parts of antioxidant.
[0010] Preferably, the TPU has a hardness of Shore A=85, a melt index value of 20 g / 10 min at 190° C. and a load of 10 kg, and an intrinsic viscosity of polycaprolactone of 0.75-1.75 dL / g;
[0011] The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate;
[0012] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
[0013] Preferably, the 3D printing material further comprises the following raw materials in parts by weight: 7 to 11 parts of carbon nanotubes and nano-attapulgite agents and 5 to 8 parts of modified filler replenishing agents;
[0014] Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is:
[0015] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 60-65° C. for 20-30 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained;
[0016] S02: irradiating the carbon nanotubes in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated carbon nanotubes after the irradiation is completed;
[0017] The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid;
[0018] S03: The preheated nano-attapulgite and modified carbon nanotube liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent.
[0019] Preferably, the modified liquid comprises the following raw materials in parts by weight:
[0020] 4-7 parts of sepiolite fiber, 1-3 parts of lanthanum nitrate solution, 2-3 parts of nano titanium dioxide, 5-8 parts of sodium silicate aqueous solution and 1-2 parts of sodium carboxymethyl cellulose.
[0021] Preferably, the mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the sodium silicate aqueous solution is 3-6%.
[0022] Preferably, the preparation method of the supplementary agent for supplementing the modified filler is:
[0023] S11: adding 4 to 7 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 5 to 8 parts of sodium lignin sulfonate solution by weight, and then adding 1 to 3 parts of citric acid, stirring sufficiently, to obtain a modified filler liquid;
[0024] S12: Stir the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then wash, filter and dry to obtain dried silicon carbide whiskers; irradiate the dried silicon carbide whiskers in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtain pretreated silicon carbide whiskers after the irradiation is completed;
[0025] S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a replenishing agent for replenishing the modified filler.
[0026] Preferably, the mass fraction of the sodium lignin sulfonate solution is 5-8%; the mass fraction of the potassium permanganate solution is 3-5%; the ultrasonic power of the ultrasonic modification treatment is 450-500 W, and the ultrasonic time is 20-30 min.
[0027] The present invention also provides a method for preparing a 3D printing material, comprising the following steps:
[0028] First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
[0029] The present invention also provides an application of a 3D printing material in a shoe material.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The 3D printing material of the present invention adopts TPU and polycaprolactone, and the antibacterial property of the product is optimized by adding functional additives such as compatibilizers, lubricants, antioxidants, and nano silver powder. At the same time, the carbon nanotubes and nano attapulgite agents and the modified filler supplementing agents are mutually coordinated to obtain the 3D printing material with optimized raw material agglomeration performance, and the antibacterial property, wear resistance and mechanical tensile property of the product are balanced and coordinated to improve, and the weather resistance and water washing stability of the product are remarkable.
[0032] The carbon nanotube blending nano-attapulgite agent uses nano-attapulgite treated with an acid solution to optimize its dispersion and activity performance, and then preheated at 60-65°C for 20-30 minutes, so that it can better match the modified carbon nanotube liquid and better blend and coordinate the raw materials. The modified carbon nanotube liquid uses carbon nanotubes as the matrix raw material, and is treated with proton irradiation to optimize the activity performance of the carbon nanotubes. The tubular carbon nanotubes with high specific surface area are used to optimize the dispersion between the raw materials. At the same time, the sepiolite fiber in the modified liquid blends the nano-titanium dioxide, and the carbon nanotube structure is reinforced to enhance the system interface and optimize the product performance balance. At the same time, lanthanum nitrate solution, sodium silicate aqueous solution and sodium carboxymethyl cellulose are combined, and the modified carbon nanotube liquid can be better matched with the preheated nano-attapulgite through the blending and coordination between the raw materials, thereby further improving the performance coordination and performance stability of the product.
[0033] The modified filler replenishing agent adopts the flake structure of flaky talcum powder interlaced reinforcement system, and then fully stirred with silane coupling agent KH550, sodium lignin sulfonate solution and citric acid to obtain a modified filler liquid, and the raw materials in the modified filler liquid are blended and assisted, and then blended with pretreated silicon carbide whiskers, and the whisker-like structure is coordinated with the modified filler liquid. Through the co-coordination and co-assistance of the raw materials, the modified filler replenishing agent and the carbon nanotube blending nano-attapulgite agent have a better synergistic effect, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] A 3D printing material of this embodiment includes the following raw materials in parts by weight:
[0036] TPU 35-40 parts, polycaprolactone 10-15 parts, nano silver powder 6-9 parts, compatibilizer 3-5 parts, foaming agent 3-4 parts, cell stabilizer 2-3 parts, lubricant 1-3 parts, antioxidant 1-3 parts.
[0037] The hardness of the TPU in this embodiment is Shore A=85, and the melt index value at 190°C and 10kg load is 20g / 10min; the intrinsic viscosity of the polycaprolactone is 0.75~1.75dL / g;
[0038] The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate;
[0039] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
[0040] The 3D printing material of this embodiment also includes the following raw materials in parts by weight: 7 to 11 parts of carbon nanotubes and nano-attapulgite agents and 5 to 8 parts of modified filler replenishing agents;
[0041] Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is:
[0042] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 60-65° C. for 20-30 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained;
[0043] S02: irradiating the carbon nanotubes in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated carbon nanotubes after the irradiation is completed;
[0044] The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid;
[0045] S03: The preheated nano-attapulgite and modified carbon nanotube liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent.
[0046] The modified solution of this embodiment includes the following raw materials in parts by weight:
[0047] 4-7 parts of sepiolite fiber, 1-3 parts of lanthanum nitrate solution, 2-3 parts of nano titanium dioxide, 5-8 parts of sodium silicate aqueous solution and 1-2 parts of sodium carboxymethyl cellulose.
[0048] The mass fraction of the lanthanum nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium silicate aqueous solution is 3-6%.
[0049] The preparation method of the supplementary agent for supplementing the modified filler of this embodiment is as follows:
[0050] S11: adding 4 to 7 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 5 to 8 parts of sodium lignin sulfonate solution by weight, and then adding 1 to 3 parts of citric acid, stirring sufficiently, to obtain a modified filler liquid;
[0051] S12: Stir the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then wash, filter and dry to obtain dried silicon carbide whiskers; irradiate the dried silicon carbide whiskers in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtain pretreated silicon carbide whiskers after the irradiation is completed;
[0052] S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a replenishing agent for replenishing the modified filler.
[0053] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5-8%; the mass fraction of the potassium permanganate solution is 3-5%; the ultrasonic power of the ultrasonic modification treatment is 450-500W, and the ultrasonic time is 20-30min.
[0054] A method for preparing a 3D printing material in this embodiment includes the following steps:
[0055] First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
[0056] The present embodiment provides an application of a 3D printing material in shoe materials.
[0057] Embodiment 1: A 3D printing material, comprising the following raw materials in parts by weight:
[0058] 35 parts of TPU, 10 parts of polycaprolactone, 6 parts of nano silver powder, 3 parts of compatibilizer, 3 parts of foaming agent, 2 parts of cell stabilizer, 1 part of lubricant, and 1 part of antioxidant.
[0059] The hardness of the TPU in this embodiment is Shore A=85, and the melt index value at 190°C and 10kg load is 20g / 10min; the intrinsic viscosity of the polycaprolactone is 0.75dL / g;
[0060] The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate;
[0061] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
[0062] The 3D printing material of this embodiment also includes the following raw materials in parts by weight: 7 parts of carbon nanotubes and nano-attapulgite agents and 5 parts of modified filler replenishing agents;
[0063] Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is:
[0064] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 60° C. for 20 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained;
[0065] S02: irradiating the carbon nanotubes in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining irradiated carbon nanotubes after the irradiation is completed;
[0066] The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid;
[0067] S03: The preheated nano-attapulgite and modified carbon nanotube liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent.
[0068] The modified solution of this embodiment includes the following raw materials in parts by weight:
[0069] 4 parts of sepiolite fiber, 1 part of lanthanum nitrate solution, 2 parts of nano titanium dioxide, 5 parts of sodium silicate aqueous solution and 1 part of sodium carboxymethyl cellulose.
[0070] The mass fraction of the lanthanum nitrate solution in this embodiment is 2%; the mass fraction of the sodium silicate aqueous solution is 3%.
[0071] The preparation method of the supplementary agent for supplementing the modified filler of this embodiment is as follows:
[0072] S11: adding 4 parts of flaky talc and 1 part of silane coupling agent KH550 to 5 parts of sodium lignin sulfonate solution by weight, and then adding 1 part of citric acid, stirring sufficiently to obtain a modified filler liquid;
[0073] S12: stirring the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then washing, filtering and drying to obtain dried silicon carbide whiskers; irradiating the dried silicon carbide whiskers in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining pretreated silicon carbide whiskers after the irradiation is completed;
[0074] S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a replenishing agent for replenishing the modified filler.
[0075] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the mass fraction of the potassium permanganate solution is 3%; the ultrasonic power of the ultrasonic modification treatment is 450W, and the ultrasonic time is 20 minutes.
[0076] A method for preparing a 3D printing material in this embodiment includes the following steps:
[0077] First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
[0078] The present embodiment provides an application of a 3D printing material in shoe materials.
[0079] Embodiment 2: A 3D printing material, comprising the following raw materials in parts by weight:
[0080] TPU 40 parts, polycaprolactone 15 parts, nano silver powder 9 parts, compatibilizer 5 parts, foaming agent 4 parts, cell stabilizer 3 parts, lubricant 3 parts, antioxidant 3 parts.
[0081] The hardness of the TPU in this embodiment is Shore A=85, and the melt index value at 190°C and 10kg load is 20g / 10min; the intrinsic viscosity of the polycaprolactone is 1.75dL / g;
[0082] The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate;
[0083] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
[0084] The 3D printing material of this embodiment also includes the following raw materials in parts by weight: 11 parts of carbon nanotubes and nano-attapulgite agents and 8 parts of modified filler replenishing agents;
[0085] Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is:
[0086] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 65° C. for 30 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained;
[0087] S02: irradiating the carbon nanotubes in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtaining irradiated carbon nanotubes after the irradiation is completed;
[0088] The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid;
[0089] S03: The preheated nano-attapulgite and modified carbon nanotube liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent.
[0090] The modified solution of this embodiment includes the following raw materials in parts by weight:
[0091] 7 parts of sepiolite fiber, 3 parts of lanthanum nitrate solution, 3 parts of nano titanium dioxide, 8 parts of sodium silicate aqueous solution and 2 parts of sodium carboxymethyl cellulose.
[0092] The mass fraction of the lanthanum nitrate solution in this embodiment is 5%; the mass fraction of the sodium silicate aqueous solution is 6%.
[0093] The preparation method of the supplementary agent for supplementing the modified filler of this embodiment is as follows:
[0094] S11: adding 7 parts of flaky talc and 2 parts of silane coupling agent KH550 to 8 parts of sodium lignin sulfonate solution by weight, and then adding 3 parts of citric acid, stirring sufficiently to obtain a modified filler liquid;
[0095] S12: stirring the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then washing, filtering and drying to obtain dried silicon carbide whiskers; irradiating the dried silicon carbide whiskers in a proton irradiation box for 10 minutes at an irradiation power of 350-400 W, and obtaining pretreated silicon carbide whiskers after the irradiation is completed;
[0096] S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a replenishing agent for replenishing the modified filler.
[0097] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 8%; the mass fraction of the potassium permanganate solution is 5%; the ultrasonic power of the ultrasonic modification treatment is 500W, and the ultrasonic time is 30min.
[0098] A method for preparing a 3D printing material in this embodiment includes the following steps:
[0099] First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
[0100] The present embodiment provides an application of a 3D printing material in shoe materials.
[0101] Embodiment 3: A 3D printing material, comprising the following raw materials in parts by weight:
[0102] 37.5 parts of TPU, 12.5 parts of polycaprolactone, 7.5 parts of nano silver powder, 4 parts of compatibilizer, 3.5 parts of foaming agent, 2.5 parts of cell stabilizer, 2 parts of lubricant, and 2 parts of antioxidant.
[0103] The hardness of the TPU in this embodiment is Shore A=85, and the melt index value at 190°C and 10kg load is 20g / 10min; the intrinsic viscosity of the polycaprolactone is 1.2dL / g;
[0104] The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate;
[0105] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
[0106] The 3D printing material of this embodiment also includes the following raw materials in parts by weight: 9 parts of carbon nanotubes and nano-attapulgite agents and 6.5 parts of modified filler replenishing agents;
[0107] Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is:
[0108] S01: The nano-attapulgite is first stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 62.5° C. for 25 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained;
[0109] S02: irradiating the carbon nanotubes in a proton irradiation box for 12.5 minutes at an irradiation power of 375 W, and obtaining irradiated carbon nanotubes after the irradiation is completed;
[0110] The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid;
[0111] S03: The preheated nano-attapulgite and modified carbon nanotube liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1250 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent.
[0112] The modified solution of this embodiment includes the following raw materials in parts by weight:
[0113] 5.5 parts of sepiolite fiber, 2 parts of lanthanum nitrate solution, 2.5 parts of nano titanium dioxide, 6.5 parts of sodium silicate aqueous solution and 1.5 parts of sodium carboxymethyl cellulose.
[0114] The mass fraction of the lanthanum nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium silicate aqueous solution is 4.5%.
[0115] The preparation method of the supplementary agent for supplementing the modified filler of this embodiment is as follows:
[0116] S11: adding 5.5 parts of flaky talc and 1.5 parts of silane coupling agent KH550 to 6.5 parts of sodium lignin sulfonate solution by weight, and then adding 2 parts of citric acid, stirring well, to obtain a modified filler solution;
[0117] S12: stirring the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then washing, filtering and drying to obtain dried silicon carbide whiskers; irradiating the dried silicon carbide whiskers in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining pretreated silicon carbide whiskers after the irradiation is completed;
[0118] S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a replenishing agent for replenishing the modified filler.
[0119] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 6.5%; the mass fraction of the potassium permanganate solution is 4%; the ultrasonic power of the ultrasonic modification treatment is 470W, and the ultrasonic time is 25min.
[0120] A method for preparing a 3D printing material in this embodiment includes the following steps:
[0121] First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
[0122] The present embodiment provides an application of a 3D printing material in shoe materials.
[0123] Comparative Example 1:
[0124] The difference from Example 3 is that no carbon nanotubes or nano-attapulgite agent is added.
[0125] Comparative Example 2:
[0126] The difference from Example 3 is that no preheated nano attapulgite is added in the preparation of the carbon nanotube-blended nano attapulgite agent.
[0127] Comparative Example 3:
[0128] The difference from Example 3 is that no modified carbon nanotube liquid is added in the preparation of the carbon nanotube-blended nano-attapulgite agent.
[0129] Comparative Example 4:
[0130] The difference from Example 3 is that no irradiated carbon nanotubes are added to the modified carbon nanotube liquid.
[0131] Comparative Example 5:
[0132] The difference from Example 3 is that no modifying liquid is added to the modified carbon nanotube liquid.
[0133] Comparative Example 6:
[0134] The difference from Example 3 is that no supplementary agent for supplementing the modified filler is added.
[0135] Comparative Example 7:
[0136] The difference from Example 3 is that no pretreated silicon carbide whiskers are added to the supplementary agent for the modified filler.
[0137] Comparative Example 8:
[0138] The difference from Example 3 is that no modified filler liquid is added to the supplementary agent for supplementing the modified filler.
[0139] Comparative Example 9:
[0140] The difference from Example 3 is that no talcum powder or silane coupling agent KH550 is added to the modified filler liquid.
[0141] The products of Examples 1 to 3 and Comparative Examples 1 to 9 were tested for antibacterial properties, wear resistance and mechanical tensile properties. At the same time, the products were subjected to ultraviolet irradiation aging treatment with an irradiation intensity of 50 mW / cm 2 , irradiated for 100 hours, and then washed with water 10 times to test the weather resistance and water washing stability of the product. The test results are shown in Table 1.
[0142] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 9:
[0143]
[0144] It can be seen from Comparative Examples 1-9 and Examples 1-3 that the product of Example 3 has excellent antibacterial properties, wear resistance and mechanical tensile properties, and the three can be improved in a coordinated manner. In addition, the product has excellent weather resistance and water washing stability;
[0145] The product does not contain any of the carbon nanotubes and nano-attapulgite agents, nor does it contain any of the modified fillers. The performance of the product deteriorates significantly, especially under weather resistance and water washing resistance conditions. The product performance effect is most significant when carbon nanotubes and nano-attapulgite agents and modified fillers are used in combination.
[0146] In the preparation of the carbon nanotube-blended nano-attapulgite, no preheated nano-attapulgite was added, no modified carbon nanotube liquid was added, no irradiated carbon nanotubes were added to the modified carbon nanotube liquid, and no modified liquid was added to the modified carbon nanotube liquid. The performance of the product showed a trend of deterioration to varying degrees. The performance effect of the product was the most significant when the specific modified carbon nanotube liquid of the present invention was combined with preheated nano-attapulgite. Other methods were not as obvious as the effect of the present invention.
[0147] The performance of the product also showed a trend of deterioration when no pretreated silicon carbide whiskers, no modified filler liquid, and no talcum powder or silane coupling agent KH550 were added to the modified filler replenishing agent for replenishing the modified filler. The modified filler replenishing agent obtained by combining the modified filler liquid obtained by the specific method of the present invention with the pretreated silicon carbide whiskers had the most significant product performance effect.
[0148] The present invention further explores the product performance through the composition of the modified liquid.
[0149] Experimental Example 1:
[0150] The only difference from Example 3 is that no sepiolite fiber is added to the modified liquid.
[0151] Experimental Example 2:
[0152] The only difference from Example 3 is that no lanthanum nitrate solution is added to the modified solution.
[0153] Experimental Example 3:
[0154] The only difference from Example 3 is that no nano titanium dioxide is added to the modified solution.
[0155] Experimental Example 4:
[0156] The only difference from Example 3 is that sodium carboxymethyl cellulose is not added to the modified solution.
[0157] Experimental Example 5:
[0158] The only difference from Example 3 is that no sodium silicate aqueous solution is added to the modified liquid.
[0159] The products of Experimental Examples 1 to 5 were tested for antibacterial properties, wear resistance and mechanical tensile properties. At the same time, the products were subjected to UV irradiation aging treatment with an irradiation intensity of 50 mW / cm 2 , irradiated for 100 hours, and then washed with water 10 times to test the weather resistance and water washing stability of the product. The test results are shown in Table 2.
[0160] Table 2 Product performance test results of Experimental Examples 1 to 5:
[0161]
[0162] It can be seen from Experimental Examples 1-5 that when sepiolite fiber is not added to the modifying liquid, the performance of the product deteriorates significantly. Secondly, when nano titanium dioxide is not added to the modifying liquid, the performance of the product also shows a significant deterioration trend. When sodium silicate aqueous solution is not added to the modifying liquid, lanthanum nitrate solution is not added to the modifying liquid, and sodium carboxymethyl cellulose is not added to the modifying liquid, the performance of the product all tends to deteriorate. Only the modifying liquid prepared by the method of the present invention has the most significant product performance effect. The composition of the modifying liquid is unique, and the effects of using other methods instead are not as significant as those of the present invention.
[0163] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0164] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A 3D printing material, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of TPU, 10-15 parts of polycaprolactone, 6-9 parts of nano silver powder, 3-5 parts of compatibilizer, 3-4 parts of foaming agent, 2-3 parts of cell stabilizer, 1-3 parts of lubricant, 1-3 parts of antioxidant, 7-11 parts of carbon nanotube and nano attapulgite agent and 5-8 parts of supplementary agent for modified filler supplementation; Wherein, the preparation method of the carbon nanotube-blended nano-attapulgite agent is: S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, then washed with water and dried, and the dried nano-attapulgite is preheated at 60-65° C. for 20-30 minutes. After the preheating is completed, the preheated nano-attapulgite is obtained; S02: irradiating the carbon nanotubes in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated carbon nanotubes after the irradiation is completed; The irradiated carbon nanotubes and the modified liquid are stirred and modified at a weight ratio of 2:5, and the stirring is completed to obtain a modified carbon nanotube liquid; S03: The preheated nano-attapulgite and the modified carbon nanotube solution are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a carbon nanotube-blended nano-attapulgite agent; The modified liquid comprises the following raw materials in parts by weight: 4-7 parts of sepiolite fiber, 1-3 parts of lanthanum nitrate solution, 2-3 parts of nano titanium dioxide, 5-8 parts of sodium silicate aqueous solution and 1-2 parts of sodium carboxymethyl cellulose; Preparation method of the modified filler replenishing agent: S11: adding 4 to 7 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 5 to 8 parts of sodium lignin sulfonate solution by weight, and then adding 1 to 3 parts of citric acid, stirring sufficiently, to obtain a modified filler liquid; S12: Stir the silicon carbide whisker in a sufficient amount of potassium permanganate solution, then wash, filter and dry to obtain dried silicon carbide whiskers; irradiate the dried silicon carbide whiskers in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtain pretreated silicon carbide whiskers after the irradiation is completed; S13: subjecting the pretreated silicon carbide whiskers and the modified filler liquid to ultrasonic modification treatment in a weight ratio of 2:5, filtering and drying after the ultrasonic modification is completed to obtain a replenishing agent for replenishing the modified filler.
2. A 3D printing material according to claim 1, characterized in that: The 3D printing material includes the following raw materials in parts by weight: 37.5 parts of TPU, 12.5 parts of polycaprolactone, 7.5 parts of nano silver powder, 4 parts of compatibilizer, 3.5 parts of foaming agent, 2.5 parts of cell stabilizer, 2 parts of lubricant, and 2 parts of antioxidant.
3. A 3D printing material according to claim 1, characterized in that: The TPU has a Shore A hardness of 85 and a melt index of 20 g / 10 min at 190° C. and a load of 10 kg; the intrinsic viscosity of the polycaprolactone is 0.75 to 1.75 dL / g; The compatibilizer is maleic anhydride; the foaming agent is azodicarbonamide; the cell stabilizer is polybutyl methacrylate; The lubricant is calcium stearate; the antioxidant is antioxidant 1010.
4. A 3D printing material according to claim 1, characterized in that: The mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the sodium silicate aqueous solution is 3-6%.
5. A 3D printing material according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 5-8%; the mass fraction of the potassium permanganate solution is 3-5%; the ultrasonic power of the ultrasonic modification treatment is 450-500W, and the ultrasonic time is 20-30min.
6. A method for preparing a 3D printing material, used for preparing a 3D printing material as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: First, the raw materials are weighed according to the weight, and then the raw materials are mixed for 30 minutes at a mixing temperature of 60°C. Then, they are sent to a twin-screw extruder for extrusion at an extrusion temperature of 170°C, granulated by a pelletizer, and then drawn by a single-screw extruder. The drawn filaments are then 3D printed, and the 3D printed products are foamed in an oven at 150°C for 20 minutes to obtain 3D printing materials.
7. Application of a 3D printing material as described in any one of claims 1 to 5 in shoe materials.
Citation Information
Patent Citations
High-elastic foamed shoe insole material, and preparation method and application thereof
CN109206892A